Fintech Dari Perspektif Perilaku User Dalam Penggunaan E-Wallet Dengan Menggunakan Technology Acceptance Model (TAM). - Gusi Putu Lestara Permana; Hesty Pahlevy Setyo Rini; I Gusti Ngurah Darma Paramartha (UNHI Press, 2021)
This study based on by interest researchers related to the development in the transaction-based fintech is an e-wallet which is the number of users of e-wallets that has increased very rapidly nowadays. The number of e-wallet uses is increasing, so the usefulness, ease of use, risk, and also the enjoyment felt by each user also varies. The purpose of this study was to determine the effect of perceived usefulness, ease of use, risk, and enjoyment of behavioral intentions in e-wallet users in Denpasar. Used data in this study is the primary data, the researchers gain from the results of the spread of the questionnaire to the respondents in Denpasar. Sampling from this study using purposive sampling. The criteria used are active users of the e-wallet application and never transact at least once using an e-wallet application. This research using 75 respondents and using an analysis of multiple regressing use SPSS software version of 25. The results of the research show that the perceived usefulness, risk, and enjoyment influential positive towards the behavior of the user, while the perceived ease of use of a negative effect on the behavior of the user.